Reference transactions to the rescue: Using Libstats to enhance library instruction, direct staff continuing education, and make effective management decisions - Theiss-White, Danielle; Coleman, Jason; Whitehair, Kristin (My University, 2008)
This poster provides an overview of how and why K-State Libraries uses Libstats, a simple, open source, Web-based system for tracking reference statistics. K-State Libraries began using Libstats at one service point in 2007, and now, three service points are using this tool to document reference transactions with very positive results. What are the benefits of using this software, and are there additional uses for it other than just tracking when reference questions are asked and by whom? The rich data compiled in Libstats can be useful for librarians needing to make evidence-based decisions about library instruction, staff training and continuing education, and reference management. The administrative side of Libstats is also displayed as well as its customizable field settings and report functions using software screen shots. The poster consists of Libstats’ screen shots, a K-State Libraries Libstats’ staff survey, a library instruction research project description with results in the form of graphs, and graphs depicting K-State Libraries' decisions based on the data.
Keywords: Reference tracking system; Web-based tracking system; Libstats; Reference management; Library staff training; Library staff continuing education; Library statistics; Library decision making; Evidence-based decision making